Developing and Communicating Effective Program Success Stories for Enhanced Accountability - John G. Richardson (Journal of Applied Communications, 1999)
This article examines the use of concise success stories to communicate program impacts to identified audiences who require or need accountability information from the North Carolina Cooperative Extension System. In this case study, anecdotal evidence is given for key groups desiring brief and concise reports of agency impacts. The procedures for developing such stories as well as faculty training needs are also discussed. The World-Wide-Web-based reporting system developed by NCCES is described in regard to its being the entry and access location for success story data. Actual examples of success stories that have been written by field and campus faculty of NCCES are also provided, with one dissected to describe the key components of such stories. While the Extension accountability system in North Carolina does not depend solely on success stories for meeting accountability requirements, such stories have been found to be quite popular with county, state and federal officials as well as to other audiences such as Extension clientele and advisory groups. The information is made available via brochures, printed fact sheets, computer presentations and the Internet.